2011
DOI: 10.1007/s13105-011-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cold-induced CYP1A activation in rat liver microsomes

Abstract: Cytochrome P4501A (the CYP1A1 and CYP1A2 enzymes) is known to metabolize anthropogenic xenobiotics to carcinogenic and mutagenic compounds. CYP1A1 transcriptional activation is regulated via the aryl hydrocarbon receptor (AhR)-dependent signal transduction pathway. CYP1A2 activation may occur through the AhR-dependent or AhR-independent signal transduction pathways. We used male Wistar rats to explore possible mechanisms of CYP1A activation induced by exposure to cold and the effects of the protein-tyrosine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…1. Previously we demonstrated that cold is a weak inducer of CYP1A in rat liver when rats were exposed to 4ºС for 5 or 10 days [9]. In the present study, we exposed rats to 4ºС for 1, 5 or 10 days.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…1. Previously we demonstrated that cold is a weak inducer of CYP1A in rat liver when rats were exposed to 4ºС for 5 or 10 days [9]. In the present study, we exposed rats to 4ºС for 1, 5 or 10 days.…”
Section: Resultsmentioning
confidence: 61%
“…The increase of activity and CYP1A apoprotein content in the liver of rats on days 5 and 10 of cooling are discussed at length in our previous report [9]. In that work we made some conclusions regarding the mechanisms of CYP1A induction in the rat liver as a result of exposure to cold: CYP1A1 is induced transcriptionally via the AhR-dependent signal transduction pathway, whereas the activation of CYP1A2 by cooling is a posttranscriptional phenomenon.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…41 Experiments on rats showed that long-term exposure to low temperature changed activities of cytochromes CYP1A1 and CYP1A2 in the liver. 42 Low temperature induced-AS chicken were under hypoxia. Couroucli (2002) discovered that hyperoxia (95% oxygenation) increases activity, mRNA and the protein level of CYP1A1 in the lungs and liver of Sprague-Dawley rats, while inversely hypoxia could restrict them.…”
Section: Systematic Analysis Of Asmentioning
confidence: 99%